2013
DOI: 10.1002/jbmr.2017
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis of the Association of Fracture Risk and Body Mass Index in Women

Abstract: Several recent studies suggest that obesity may be a risk factor for fracture. The aim of this study was to investigate the association between body mass index (BMI) and future fracture risk at different skeletal sites. In prospective cohorts from more than 25 countries, baseline data on BMI were available in 398,610 women with an average age of 63 (range, 20-105) years and follow up of 2.2 million person-years during which 30,280 osteoporotic fractures (6457 hip fractures) occurred. Femoral neck BMD was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

27
290
4
17

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 419 publications
(338 citation statements)
references
References 63 publications
27
290
4
17
Order By: Relevance
“…It is also of interest that obesity (BMI ≥30 kg/m 2 ) may reduce the risk of hip fractures in women 29. Additionally, the prognosis of COPD is worsened by the presence of comorbid illnesses such as hypertension and diabetes mellitus 30.…”
Section: Discussionmentioning
confidence: 99%
“…It is also of interest that obesity (BMI ≥30 kg/m 2 ) may reduce the risk of hip fractures in women 29. Additionally, the prognosis of COPD is worsened by the presence of comorbid illnesses such as hypertension and diabetes mellitus 30.…”
Section: Discussionmentioning
confidence: 99%
“…15,79,80 A BMI of o21 kg m À 2 or a body weight of o127 pounds is associated with increased risk of low BMD and increased fracture risk in women. 15 There is a strong correlation between BMD and BMI, and several studies have shown that a decrease in body weight leads to bone loss.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…81 A recent meta-analysis investigated the association between BMI and future fracture risk at different skeletal sites and concluded that low BMI remains a risk factor for hip and all osteoporotic fractures. 80 Even when adjusted for BMD, low BMI remains a risk factor for hip fracture. 15,80 BMI is more predictive of osteoporosis than is weight alone.…”
Section: Body Mass Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…(14)(15)(16) A recent meta-analysis examined the association between BMI and fracture risk in prospective cohorts from 25 countries (398,610 women with an average age of 63 years; 2.2 million person-years follow-up) with a reported 22% prevalence of obesity. (17) Risk for major osteoporotic fractures and hip fractures decreased monotonically with increasing BMI when the modifying effect of BMD was excluded. When BMD was considered, the effect of BMI was greatly reduced and, at least for major osteoporotic fractures, showed a biphasic response such that fracture risk decreased as BMI increased to the normal range and then slightly increased for overweight and obese individuals.…”
mentioning
confidence: 94%